The role of Media literacy for parents and social identity with media consumption students - jafar bahadorikhosroshahi; isa bargi (مطالعات رسانه‌های نوین, 2018)
The aim of this study was to the role of Media literacy for parents and social identity with media consumption students. The study was descriptive and correlational. The statistical community of the present study teenagers ranging 18 - 11 years studying inschools in the city of Ilkhechi (Tabriz) in the academic year 2015-2016 and their parents ofsociety, the number of 123 people cluster random sampling method bailout between schools in the city of Ilkhechi have been chosen and investigated. To collect the data, and media consumption, media literacy and social identity were parents. Data analysis using Pearson correlation coefficient and stepwise regression analysis was performed. The results showed that parents' media literacy social media consumption in adolescents is a significant positive relationship. Multiple regression analysis also showed that access to and use of the media, the ability to analyze and evaluate, individual and social identity, critical thinking, media and communication with media messages are able to predict the consumption of media, TV, radio, press, the Internet and mobile phones. According to media literacy and social identity so parents can have an important role in media consumption among adolescents.